2018
DOI: 10.1155/2018/4957917
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Disintegration Mechanism of Deep Rock Masses under Coupled High Axial Geostress and Blasting Load

Abstract: Zonal disintegration phenomenon with alternative distribution of fracture zones and nonfracture zones is a characteristic failure in deep rock masses, especially for deep tunnel excavated by drill and blast method. To investigate the mechanism of zonal disintegration under coupled high axial geostress and blasting load, elastic stress field distribution for a circular tunnel in deep isotropic rock masses is obtained. Furthermore, Hoek-Brown criterion is amended by considering blast-induced damage effect. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…When first ring fracture occurs around excavated tunnel, it is equivalent to a bigger excavated tunnel in deep rock mass [17]. Due to blasting damage in deep rock mass around excavated tunnel, ring fractures are much easier to happen and fractures near the excavated tunnel are more severe under high axial geostress condition [28]. The final shape and size of excavated tunnel can be obtained by measuring the cut rectangular cemented sand model.…”
Section: Fracture Forms Around Excavated Tunnelmentioning
confidence: 99%
See 1 more Smart Citation
“…When first ring fracture occurs around excavated tunnel, it is equivalent to a bigger excavated tunnel in deep rock mass [17]. Due to blasting damage in deep rock mass around excavated tunnel, ring fractures are much easier to happen and fractures near the excavated tunnel are more severe under high axial geostress condition [28]. The final shape and size of excavated tunnel can be obtained by measuring the cut rectangular cemented sand model.…”
Section: Fracture Forms Around Excavated Tunnelmentioning
confidence: 99%
“…Due to the blasting excavation, blasting load effect not only applies a transient load on cemented sand model, but also induces many damages and cracks in cemented sand model and deteriorates its mechanical properties [20]. Moreover, blasting load plays a significant role on the first fracture zone for its rapid attenuation, and it will expand the radius and width of first fractur zone [28]. Therefore, radius scale factor, 1.28, is a little smaller than 1.4 in the research of Chen et al [29].…”
Section: Fracture Forms Around Excavated Tunnelmentioning
confidence: 99%
“…Han et al [20] found that flaw inclination angle and ligament angle remarkably affected dynamic compressive strength and dynamic deformation properties, respectively. Liu et al [21] comparatively analyzed energy consumption properties of vertical bedded and parallel bedded coal-rock and observed that more energy would be needed by vertical bedded coal-rock for the same fractal dimension. Yuan et al [22] investigated the effect of joint angle on zonal disintegration under coupled high in situ axial stress and blasting load and found that the number of cracks after blasting and released strain energy had similar variable tendency.…”
Section: Introductionmentioning
confidence: 99%
“…However, some scholars believed that rock mass around the excavation was subjected to dynamic loading during the excavation process. Annular zonal fractures were obtained by using the General Particle Dynamics (GPD) method [20,21].…”
Section: Introductionmentioning
confidence: 99%